Research on the distribution, localization, and morphology of fluorides in the cell walls of tea plant leaves - Li, Chunlei; Xu, Hongmei; Xu, Jing; Luo, Jinlei; Li, Peizhi; Zhao, Fei (Frontiers in Plant Science, 2025)
Tea plant leaves exhibit fluorine-accumulating properties, and the excessive intake of fluoride (F) via tea consumption may pose health risks to consumers; however, despite the high-F content in tea plant, signs of F toxicity are absent, suggesting the presence of F tolerance mechanisms within tea plant. This study investigated F accumulation in the cell walls and structural composition of cell walls in leaves of two tea plant varieties from tea gardens: Camellia sinensis cv. Nongkangzao, a high-F cultivar, and C. sinensis cv. Pingyang Tezao, a low-F cultivar. The results indicate that cell walls are the primary site of F accumulation in tea leaves, accounting for greater than 80.8% of total F, primarily in a water-soluble form. Furthermore, the F in tea leaf cell walls is predominantly located within pectin polysaccharides. In the leaves of Nongkangzao and Pingyang Tezao, the F in pectin accounted for 83.2% and 89.6% of cell wall F, respectively. The fluoride in the cell wall components shows a significant correlation with the metal elements Al, Ca, Mn, and K. The cell wall modifications show that fluoride is closely associated with the amino and carboxyl groups in pectin. Thus, this study aimed to provide an in-depth analysis of the role of tea plant leaf cell walls in F accumulation. In summary, we hypothesize that F in tea plant may directly bind to the amino and carboxyl groups in pectin, or it may bind together with metal elements at these sites in pectin, thereby being fixed within the cell wall. This prevents fluoride from further entering the cell interior and mitigates its damaging effects on intracellular structures. This may be a key mechanism underlying the F tolerance in tea plants.